Rural-urban and geographical differences in prognosis of atrial fibrillation in Finland: a nationwide cohort study - Teppo Konsta; Airaksinen K. E. Juhani; Halminen Olli; Jaakkola Jussi; Linna Miika; Haukka Jari; Putaala Jukka; Mustonen Pirjo; Kinnunen Janne; Hartikainen Juha; Lehto Mika (SAGE PUBLICATIONS LTD, 2025)
Aims: Rural-urban disparities have been reported in the outcomes of cardiovascular diseases. We assessed whether rural-urban or other geographical disparities exist in the risk of ischemic stroke (IS) and death in patients with atrial fibrillation (AF) in Finland.
Methods: The registry-based FinACAF cohort study covers all patients with AF from all levels of care in Finland from 2007 to 2018. Patients were divided into rural-urban categories and into hospital districts (HDs) based on their municipality of residence.
Results: We identified 222,051 patients (50.1% female; mean age 72.8 years; mean follow-up 3.9 years) with new-onset AF, of whom 15,567 (7.0%) patients suffered IS and 72,565 (32.7%) died during follow-up. The crude IS rate was similar between rural and urban areas, whereas the mortality rate was lower in urban areas (incidence rate ratios (IRRs) with 95% confidence intervals (CIs) 0.97 (0.93-1.00) and 0.92 (0.91-0.93), respectively). However, after adjustments, urban residence was associated with slightly higher IS and mortality rates (IRRs with 95% CIs 1.05 (1.01-1.08) and 1.06 (1.04-1.07), respectively). The highest crude IS rate was in the East Savo HD and the lowest in & ANGS;land, whereas the highest crude mortality rate was in the Lansi-Pohja HD and the lowest in the North Ostrobothnia HD (IRRs with 95% CIs compared to Helsinki and Uusimaa HD for IS 1.46 (1.28-1.67) and 0.79 (0.62-1.01), and mortality 1.24 (1.16-1.32) and 0.97 (0.93-1.00), respectively. Conclusions: Rural-urban differences in prognosis of AF in Finland appear minimal, whereas considerable disparities exist between HDs.